Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan Di PT. Sukses Mitra Sejahtera (SMS) - Eka Aidina, Amalia; Munir, Miftahul; Kusuma Wardhani, Rike (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to determine the influence of discipline and work motivation on employee performance at PT. Mitra Sejahtera Success (SMS). The variables in this research are work discipline (X1), work motivation (X2), and employee performance (Y). This research uses quantitative methods using data collection techniques in the form of interviews, observations, literature studies and questionnaires. Meanwhile, the analysis used is the validity test, reliability test, classical assumption test, multiple linear regression test, t test and f test as well as the coefficient of determination. Sampling in this study used purposive sampling taking into account all employees of PT. Sukses Mitra Sejahtera (SMS) totaling 46 people based on the results of research conducted. The results of this research use the SPSS 25.0 program using a significance level of 5% or 0.05 with results (1) partially work discipline has a significant effect on employee performance, which means H1 is accepted and H01 is rejected. (2) partially work motivation has a significant effect on employee performance, which means H2 is accepted and H02 is rejected. (3) simultaneously work discipline and work motivation have a significant effect on employee performance, which means Ha3 is accepted and H03 is rejected.